2020
DOI: 10.1108/jpmh-04-2020-0030
|View full text |Cite
|
Sign up to set email alerts
|

Using a storytelling intervention in schools to explore death, dying, and loss

Abstract: Purpose Experiencing bereavement in childhood can cause profound changes to developmental trajectories. This paper aims to evaluate the feasibility of implementing a public health intervention in schools to encourage pupils aged 12-15 years to independently explore ideas of death, dying, loss and end of life care in a structured and creative format. Design/methodology/approach A co-produced storytelling intervention was implemented in an independent school in Norwich, UK. Pupils wrote up to 1,000 words in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
(35 reference statements)
0
4
0
Order By: Relevance
“…Stories can help children understand that everyone grieves differently, and teachers can also open up conversations about grief, death, and loss by encouraging pupils to research bereavement customs in other countries or different historical periods (Jackson & Colwell, 2002). Creative approaches can also provide a safe space for young people to explore these ideas: for example, Blake et al (2020) reported that secondary-school pupils in Norwich, England, were more confident in thinking and talking about death after taking part in a storytelling project about bereavement, and the St Christopher's Schools Programme ran 34 arts-based projects to bring together schools and hospices or care homes in London between 2005 and 2011 (Tsiris et al, 2011). Charities and organisations have created a variety of different lesson plans which help teachers 'distance the learning' through using stories (for example, Child Bereavement UK's 'Elephant's Tea Party' for learners aged 5-14 and many of the PSHE-Association-accredited Winston's Wish lesson plans for learners aged 5-16) or creative activities coupled with discussion questions (such as the online toolkit recently released by Child Bereavement UK in collaboration with Learning Grid for London, 'Having honest conversations about death and grief ', for learners aged 5-16).…”
Section: Are There Sufficient Resources To Support Sensitive Grief Ed...mentioning
confidence: 99%
“…Stories can help children understand that everyone grieves differently, and teachers can also open up conversations about grief, death, and loss by encouraging pupils to research bereavement customs in other countries or different historical periods (Jackson & Colwell, 2002). Creative approaches can also provide a safe space for young people to explore these ideas: for example, Blake et al (2020) reported that secondary-school pupils in Norwich, England, were more confident in thinking and talking about death after taking part in a storytelling project about bereavement, and the St Christopher's Schools Programme ran 34 arts-based projects to bring together schools and hospices or care homes in London between 2005 and 2011 (Tsiris et al, 2011). Charities and organisations have created a variety of different lesson plans which help teachers 'distance the learning' through using stories (for example, Child Bereavement UK's 'Elephant's Tea Party' for learners aged 5-14 and many of the PSHE-Association-accredited Winston's Wish lesson plans for learners aged 5-16) or creative activities coupled with discussion questions (such as the online toolkit recently released by Child Bereavement UK in collaboration with Learning Grid for London, 'Having honest conversations about death and grief ', for learners aged 5-16).…”
Section: Are There Sufficient Resources To Support Sensitive Grief Ed...mentioning
confidence: 99%
“…However, school is a useful and versatile context to provide students with a sense of normality and a distraction from their illness or life situation, while providing long-term goals and a strong social connection (Ramos et al, 2018). Blake et al (2020) highlight the practical implications of considering educational settings as anchor institutions to support a public health approach to end-oflife care, as schools are valuable assets in supporting children and families affected by death, illness, and bereavement. In this regard, Wadley et al (2014) described the impact that prolonged absence from school can have on children, such as isolation from friends and disruption of learning.…”
Section: The Transformative School As An Instrument Of Changementioning
confidence: 99%
“…In summary, the literature suggests the importance of treating children's grief with an approach that allows them to think and talk about their feelings and remember the person they lost. The nature of the recommended strategies allows for active engagement and creative exploration which appears to contribute to greater psychological preparedness and resilience in the face of death and loss, reducing the risk of negative developmental outcomes and complex grief (Blake et al, 2020).…”
Section: Rethinking Classroom Actions and Proposals For Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, in the last two decades, there has been a push to increase death and grief education in schools (even to make it mandatory, see Dawson et al, 2023) using different tools such as photovoice Bereavement: Journal of grief and responses to death • Vol. 3 (2024) • https://www.bereavementjournal.org (Raccichini et al, 2023), storytelling (Blake et al, 2020), psychodrama (Testoni et al, 2018), and music (Tsiris et al, 2011), to mention a few approaches.…”
Section: The Historical Absence Of Death Educationmentioning
confidence: 99%